2019
DOI: 10.1111/hdi.12730
|View full text |Cite
|
Sign up to set email alerts
|

Statin use among Veterans with dialysis‐dependent chronic kidney disease

Abstract: Introduction: The benefits of statin medications in patients receiving maintenance dialysis remains controversial and clinical trials overall have shown no benefit. Potential side effects of statin medications include myalgias, myopathy, and memory loss and risk of side effects associated with statin medications increase with higher statin doses. We examined statin use and statin dose among Veterans with dialysis dependent CKD. Such information may help clinicians modulate medication use and reduce pill burden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Chronic kidney disease (CKD) increases the risk of dementia, damages the cerebrovascular system, and promotes WMH in the prefrontal cortex in animal models ( Viggiano et al, 2020 ). The beneficial effects of statin therapy for CVD in patients with CKD remain controversial, and the cognitive effect of statins is rather unknown in the CKD population ( Markossian et al, 2019 ). Recently, Zijlstra et al (2020) investigated the association between kidney function and cognitive decline in older adults at high risk of CVD, using data from the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER).…”
Section: Individual-related Factorsmentioning
confidence: 99%
“…Chronic kidney disease (CKD) increases the risk of dementia, damages the cerebrovascular system, and promotes WMH in the prefrontal cortex in animal models ( Viggiano et al, 2020 ). The beneficial effects of statin therapy for CVD in patients with CKD remain controversial, and the cognitive effect of statins is rather unknown in the CKD population ( Markossian et al, 2019 ). Recently, Zijlstra et al (2020) investigated the association between kidney function and cognitive decline in older adults at high risk of CVD, using data from the Prospective Study of Pravastatin in the Elderly at Risk (PROSPER).…”
Section: Individual-related Factorsmentioning
confidence: 99%
“…8 However, recent studies have disclosed potential health and safety hazards related to prolonged statin administration, including myalgias, myopathy and memory loss. 9 A few studies confirmed that the nutrients and secondary metabolites in plant fermentation broth are potently antioxidant and can restore health by improving antioxidant capacity, restoring oxidation/ antioxidant homeostasis and lowering lipid levels. 10 Plant fermentation broth is rich in polyphenols, flavonoids and probiotics.…”
Section: Introductionmentioning
confidence: 99%